FORCE CONSTANTS IN MONOCRYSTALS OF KRYPTON - MEJIA, CR (UNAM, Ctr Invest Mat, 1976)
Abstract only given, as follows: Using the work of W.B. Daniels et al. in which they reported the dispersion relations for phonons corresponding to the [100], [110] and [111] directions in monocrystals of krypton measured at 79 degrees K and 2.31 kbar, th
THE AUK
Keywords: FORCE, CONSTANTS, MONOCRYSTALS, KRYPTON; FISICA; FISICA MOLECULAR; ESTRUCTURA MOLECULAR